2020
DOI: 10.1088/1757-899x/750/1/012036
|View full text |Cite
|
Sign up to set email alerts
|

Research on ESP Teaching in Post MOOC Applied Universities Based on SPOC Model

Abstract: Following the development of globalization, various industries not only in their own country, but also in the whole world, the relationship between peers is closer, the scale of technology exchange, experience exchange, research results exchange is gradually expanding, the gap of applied English talents is increasing, and more demands are put forward for the training and teaching of specialized English skilled personnel. Under the vigorous expansion situation of MOOC and SPOC, this paper introduces the concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Their background includes the movement toward open educational resources and pioneering initiatives in distance education with digital technology (Berrocoso et al, 2020, p.51). Kang (2019) showed that MOOCs involve a wide range of learning groups, while SPOCs and their specific requirements for a particular ESP level are for small groups. A combination of MOOCs and SPOCs contributes to the development and innovation in teaching professional foreign languages (Kang, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their background includes the movement toward open educational resources and pioneering initiatives in distance education with digital technology (Berrocoso et al, 2020, p.51). Kang (2019) showed that MOOCs involve a wide range of learning groups, while SPOCs and their specific requirements for a particular ESP level are for small groups. A combination of MOOCs and SPOCs contributes to the development and innovation in teaching professional foreign languages (Kang, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Kang (2019) showed that MOOCs involve a wide range of learning groups, while SPOCs and their specific requirements for a particular ESP level are for small groups. A combination of MOOCs and SPOCs contributes to the development and innovation in teaching professional foreign languages (Kang, 2019). According to Datsun (2019, p.162), student motivation and satisfaction with the educational process were increased by SPOCs in European universities.…”
Section: Introductionmentioning
confidence: 99%